Key concepts in operations management - Leseure, Michel (Los Angeles SAGE, 2010)
"Over 50 concept entries include: Operations Strategy, Managing Innovation, Process Modeling, New Product Development, Forecasting, Planning and Control, Supply Chain Management, Risk Management and many more."--Publisher.
Keywords: Production management